Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Obyek Wisata Air Terjun Mauhalek - Antonia Filomena Mau (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2021)
This research aims to analyze and study service facilities for tourist attraction, service facilities for tourist satisfaction, tourist attraction to tourist satisfaction, tourist satisfaction with a wealth of tourist attractions. the influence of service facilities on income through tourist satisfaction path coefficients and the effect of tourist attraction on tourist revenue through the coefficient of tourist route lane in Belu Regency. The results showed that the monthly monthly retribution of mauhalek waterfalls from July to October was relatively low due to a lack of attention from the local government in facilitating tourist attractions so that tourist interest sometimes declined. The data used is path analysis (path analysis) which used primary data obtained through the distribution of questionnaires.